2023
DOI: 10.1001/jamanetworkopen.2023.19583
|View full text |Cite
|
Sign up to set email alerts
|

In-Hospital Deaths From Ambulatory Care–Sensitive Conditions Before and During the COVID-19 Pandemic in Japan

Abstract: ImportanceThe COVID-19 pandemic may have played a role in the deterioration of access to medical care for ambulatory care–sensitive conditions (ACSCs).ObjectiveTo ascertain whether the number of in-hospital deaths and in-hospital mortality rate associated with ACSC changed after the declaration of the COVID-19 national state of emergency in Japan.Design, Setting, and ParticipantsThis cohort study used a difference-in-differences design to compare outcomes for ACSC in the period before (January 1, 2015, to Dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…This is especially evident in vaccine-preventable ACSC hospitalizations. Increased in-hospital mortality rates of ACSC-related hospitalizations during the COVID-19 pandemic have also been reported by other authors [38]. On the one hand, this could suggest that patients, for some reason, did not seek help on time, as was already shown for acute coronary syndrome [39,40].…”
Section: Comparisons With Other Studiessupporting
confidence: 59%
“…This is especially evident in vaccine-preventable ACSC hospitalizations. Increased in-hospital mortality rates of ACSC-related hospitalizations during the COVID-19 pandemic have also been reported by other authors [38]. On the one hand, this could suggest that patients, for some reason, did not seek help on time, as was already shown for acute coronary syndrome [39,40].…”
Section: Comparisons With Other Studiessupporting
confidence: 59%
“…These findings follow similar trends observed in other countries despite their differences in health systems, sociocultural contexts and experiences of COVID-19. [15][16][17][18] We extend this work through analysing a longer time period and through detailed disaggregated by markers of socioeconomic inequality. Our results also follow observations for other metrics including falls in non-COVID-19 mortality.…”
Section: Discussionmentioning
confidence: 97%
“…10 Research has shown that avoidable hospitalisations in many countries fell in 2020 during the first COVID-19 waves and did not return to pre-pandemic levels thereafter. [15][16][17][18] Most of this research, however, stops at the end of 2020 and there is less understanding of how trends have continued since. This ignores a critical period in the response and recovery from the pandemic.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%